LIKUIDITAS, LEVERAGE, DAN PERTUMBUHAN ENTITAS TERHADAP NILAI PERUSAHAAN - Rudi Setiadi Tjahjono; Rahayu Setiyowati (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to obtain empirical evidence regarding the influence of independent variables, namely profitability (ROA), liquidity (CR), company size (SIZE), leverage (DAR), managerial ownership (MO), asset growth (AG), and institutional ownership (IO) on the dependent variable, namely company value (PBV). The population used in this study was all non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2020. Sampling using the purposive sampling method, there were 98 non-financial companies that matched the criteria used in this study. The data of this study were analyzed using the multiple regression method. The results of this study show that profitability (ROA) and leverage (DAR), positively affects the value of the company (PBV). Meanwhile, asset growth (AG) negatively affects the company's value (PBV). But liquidity (CR), company size (SIZE), managerial ownership (MO), and institutional ownership (IO) have no effect on the value of the company (PBV).